Dynamic simulation of an indirect partial oxidation reactor for methane conversion to hydrogen - Karakaya, Mustafa. (Thesis (M.S.)-Bogazici University. Institute for Graduate Studies in Science and Engineering, 2006., 2006)
The steady and dynamic behavior of a catalytic indirect partial oxidation (combinedtotal oxidation/steam reforming) reactor for the conversion of methane to hydrogen isinvestigated using computer-based modeling/simulation techniques. A one-dimensional pseudohomogeneous reactor model is employed for the description of autothermal conversionof methane over a physical mixture of Pt/?-Al2O3 and Ni/MgO-Al2O3 -catalysts. Steady-stateand dynamic simulation of the bench-scale reactor is carried out for a set of different feedconditions. Transients during the start-up of the autothermal reforming process are analyzed,and the steady values of the system variables such as temperature and product flow rates are compared with those obtained from the steady-state simulations. The dynamic response of thereactor which is initially at steady state to a disturbance in the feed is also analyzed. Theresponse to a step change that involves an increase in the inlet oxygen flow rate is the elevation of temperature, which in turn leads to higher product yields. If the disturbanceinvolves an increase in the steam flow rate, the temperature and product yields decrease intime to a local minimum, and from that moment onwards, they gradually increase to thesubsequent steady state. The size of an indirect partial oxidation reactor for producing 1.5 kW-fuel-cell-grade hydrogen is determined by steady-state simulations and trial-and-error for different feed conditions.
Keywords: Fuel cells.; Hydrogen.; Methane.